Accelerated idioventricular rhythm before reperfusion What does it mean? A case report - Cueva Parra, Angel David (2021)
Accelerated idioventricular rhythm has traditionally been recognized as a benign arrhythmia. In the context of an acute myocardial infarction is a marker of successful reperfusion, however the evidence is controversial. Usually, this arrhythmia is transitory and does not cause hemodynamic compromise, however its presence may have prognostic value and not necessarily be a benign marker. The recognition of this arrhythmia is always important as well as its documentation on a 12-lead electrocardiogram. We present the case of an adult male patient with inferior ST-segment elevation myocardial infarction, who presented accelerated idioventricular rhythm without reperfusion therapy.